OCCUPATIONAL FACTORS ASSOCIATED WITH DEPRESSION IN NURSES WORKING IN A FEDERAL GOVERNMENT TERTIARY CARE HOSPITAL IN ISLAMABAD - Bukhari, Gul Mehar Javaid; Habibullah, Shaista; Abbasi, Mudassar Mushtaq Jawad; Malik, Javeria Saleem (Journal of Ayub Medical College Abbottabad, 2019)
Background: Depression is more prevalent in women than in men. Among women’s population sub-groups, there is paucity of research regarding occupational factors associated with depression in Pakistani nurses. Methods: This cross-sectional study was conducted on 250 female nurses working in a Federal Government tertiary care hospital in Islamabad. Pretested modified form of Agha Khan University Anxiety and Depression Scale was used to collect primary data. The questionnaires collected data on depressive symptoms, work experience, working hours, working environment, harassment by patients or attendants, job satisfaction and job stress. SPSS version 20 was used for data analysis. Chi-square test was used to see the association between different variables and depression. Results: This study indicated high level of depression in nurses who were having work experience of 5-7 years (p=0.000), who were working on rotating shifts (p=0.012), whose work hours were not flexible (p=0.032), who had experienced verbal abuse or harassment by patient or attendant (p=0.001), who thought that they had more responsibilities and less authorities at work (p=0.018), who suffered from injury at work (p=0.010), who thought that they had to work fast at job (p=0.004), who thought that they had to do extra physical work at job (p=0.003), who believed that they had insufficient time for patient care (p=0.006), who were not allowed to take decisions according to patient’s requirements (p=0.005), who were neither appreciated nor received any feedback from their seniors (p=0.002), who did not enjoy their work (p=0.001), who did not enjoy relations with their colleagues (p=0.001), who were harassed by their administration (p=0.000), who were not satisfied from their job (p=0.012) and who believed that their job is stressful (p=0.000). Conclusion: This study concluded that occupational factors play a very important role in determining depression in Pakistani nurses. Keywords: Depression; Working Environment; Job Satisfaction; Job Stress